Investigations on Laser Forming of Flat Glasses. (2015) - Bliedtner, J.; Barz, A.; Hecht, K.; Schwager, A.-M.
Abstract: A modified high-power laser system with an output power of 2.0 kW and an effective focus diameter of 1 mm allows a flexible forming of flat glass products. Due to the high absorption of most glasses in the mid infrared wave length range the CO2 -laser can be used very efficiently. The investigations show the potential of laser radiation for the partial forming of flat glass and the formability of glass materials depending on material thickness and the thermal expansion coefficient. Smaller and smaller glass components with more complex geometries can be processed because of the high focusability of the laser beam. With this intensity, it was possible to achieve forming depths of up to 6 mm. Another part of the studies is the creation of mechanical stress and its minimisation for which photoelastic methods as well as the differential interference contrast microscopy are used. The new technology can be applied especially in the fields of display glasses, sensor and medical technology.